2018
DOI: 10.21037/jtd.2018.09.62
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral embolic protection devices during transcatheter aortic valve implantation: clinical versus silent embolism

Abstract: Cerebrovascular events following transcatheter aortic valve implantation (TAVI) is one of the most devastating complications. Several studies with magnetic resonance or cerebral filters have demonstrated the universal brain embolization after TAVI, in the majority of patients clinically silent. Embolic protection devices (EPD) have been developed as a mechanical barrier to prevent these emboli to reach cerebral vasculature and potentially reduce neurological events. We review the current evidence about EPD in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
0
17
1
Order By: Relevance
“…Cerebral embolic protection devices (CEPDs) have been developed to work as a mechanical barrier to prevent embolic debris from reaching the cerebral vasculature, potentially reducing neurological events during TAVR procedures. The dual-filter-based Sentinel TM Cerebral Protection System (Sentinel) (Boston Scientific, Marlborough, MA, USA) received CE Mark approval in 2013 and Food and Drug Administration (FDA) approval in 2017, and it is now the most widely used CEPD system [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral embolic protection devices (CEPDs) have been developed to work as a mechanical barrier to prevent embolic debris from reaching the cerebral vasculature, potentially reducing neurological events during TAVR procedures. The dual-filter-based Sentinel TM Cerebral Protection System (Sentinel) (Boston Scientific, Marlborough, MA, USA) received CE Mark approval in 2013 and Food and Drug Administration (FDA) approval in 2017, and it is now the most widely used CEPD system [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…CVEs are associated with increased 1-year mortality [ 41 , 42 ], are independent predictors of morbidity during the follow-up and have a major impact on quality of life, by impairing cognitive function and daily abilities [ 43 , 44 ]. CVEs are largely underdiagnosed, mainly due to the absence of a standardized definition and classification [ 44 ], with a thorough neurological examination not part of the routine check-ups after TAVI.…”
Section: Cerebral Protection Devices For Stroke Preventionmentioning
confidence: 99%
“…CPDs can be classified in capturing filters or deflectors: capturing filter devices can retain embolic material while deflector devices reject it towards the descending aorta [ 44 ].…”
Section: Cerebral Protection Devices For Stroke Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggested that CEPD use is associated with less overt strokes, lower total lesion volume, and a smaller number of new ischemic lesions detected by post-procedural magnetic resonance imaging (MRI) studies [10,[16][17][18][19] .…”
Section: Cerebral Protection Systemmentioning
confidence: 99%